2003
DOI: 10.1021/jp036319y
|View full text |Cite
|
Sign up to set email alerts
|

Electrodesorption Potentials of Self-Assembled Alkanethiolate Monolayers on Copper Electrodes. An Experimental and Theoretical Study

Abstract: Electrodesorption potentials for alkanethiolate self-assembled monolayers (SAMs) on polycrystalline Cu and Cu(111) surfaces were determined by using electrochemical techniques combined with Auger electron spectroscopy. For a given alkanethiolate SAM, the electrodesorption potentials from Cu are shifted 0.6 V in the negative direction with respect to those found on Au. Calculations based on density funtional theory for methanethiolate desorption from Cu(111) show that these potential differences reflect differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
67
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 77 publications
(141 reference statements)
4
67
0
Order By: Relevance
“…SAMs on copper were proposed to be more stable than those formed on gold surfaces, indicating high stability of SAMs on copper surfaces (Azzaroni et al, 2003); this observation is in agreement with other reported data where the stronger chemisorption interaction on the copper surface was explained in terms of the atomic properties, i.e., the differences in a radial distribution of the valence (n + 1) s atomic orbitals (Akinaga et al, 2001). …”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…SAMs on copper were proposed to be more stable than those formed on gold surfaces, indicating high stability of SAMs on copper surfaces (Azzaroni et al, 2003); this observation is in agreement with other reported data where the stronger chemisorption interaction on the copper surface was explained in terms of the atomic properties, i.e., the differences in a radial distribution of the valence (n + 1) s atomic orbitals (Akinaga et al, 2001). …”
Section: Introductionsupporting
confidence: 91%
“…Assemblies based on thiols on gold are the most extensively studied SAMs (Persson et al, 1999;Rosario-Castro et al, 2006;Azzaroni et al, 2003;John et al, 2000) because of the high stability of gold in different environments and the easy preparation of clean gold surfaces (Akinaga et al, 2001). On the other hand, alkanethiols assembled on other metals like copper and silver are more difficult to work with because of the sensitivity and stability of these systems to air exposure and long exposure to the solution containing the thiol (Laibinis et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the rotating disc-ring technique has been used for the E p determination. [24] The electrode consisted in a alkanethiolate-covered Cu disc and Au ring. The ring potential was held at À0.2 V so that when the applied potential to the Cu disc reaches E p , the desorbed alkanethiolates [Reaction (2)] are electroadsorbed on the Au ring [Reaction (1)] leading to a detectable positive (anodic) current (Figure 5c).…”
Section: Electrochemical Stability Of Samsmentioning
confidence: 99%
“…On the other hand, for a constant n the stability of alkanethiolates increases in the following order Au < Ag < Cu (Figure 8). [24] Density functional theory calculations [24] have shown that the electrodesorption potential for a given alkanethiol on different metals results from a balance between the adsorption energy of the organic molecule on the metal surface (which varies in the 40-60 kcal mol À1 range), the energy to introduce an electron into the alkanethiolate-metal system, and the solvation of the metal surface.…”
Section: Electrochemical Stability Of Samsmentioning
confidence: 99%
“…Other interesting features, which are out of the scope of this chapter, about the reductive desorption of organothiolate SAMs from a metal surface include the micelle-like aggregates that are formed after the desorption [11,12,25,71], the appearance of multiple peaks on the n voltammogram [9,31,33,72], the effects of pH [44], the reoxidative adsorption after the desorption [11,[73][74][75], the effect of the nature of the metal and the facets on SAMs [10,19,[76][77][78][79], the role of solvents used for the formation of SAMs [27,80], the effect of the type of ω-terminal on the desorption behavior [3,14,34,38,81], the rate of the ion penetration [1], the effect of the temperature on the shape of voltammograms [82], and the desorption of SAMs other than alkanethiols [23,24,32,49,50,53,[83][84][85][86].…”
mentioning
confidence: 99%